Impact of Recruitment And Selection Process on Organizational Performance - R Bharth Vajan,; A Devendran,; K. Ananthasuresh,; S V Elumalayan, (International Journal of Psychosocial Rehabilitation, 2020)
The present study is to focus on to find the impact of Recruitment and selection Process in Organizational Performance conducted in Pageone Technologies, Chennai aims to find out the general opinion of the Recruitment and selection process attended by the employees at Pageone Technologies. The main objective of project is to study the process of Recruitment in Pageone Technologies. The secondary objectives are to assess the perception of the employers regarding Talent hunt process they have undergone, to identify whether the Recruitment is done from internal or external sources, to analyze the effectiveness of Talent Acquisition to identify the factors of recruitment and selection process, to identify new ways of improving the present recruitment procedure, to identify the average time spent for selection process1. The need for this project is to define the current and potential needs of the workforce preparation and role analysis activities of the company, to clarify the recruitment and selection process in company and to analysis of the time management in the recruitment process. This research papers helps to make decision in selecting the right candidates for the right job, this study helps the organization to identify the area of problem and suggest ways to improve the Talent and selection process, this study focus on understanding Talent and selection process this study helps to manage a manpower budget for the recruitment and selection Method, this study assists in determining the time limit for the recruitment process. Most of the employees were satisfied but changes are required according to the changing scenario as Talent process has a great impact on the working of the company as a new blood, new idea enters in the company